Assessment of the Logistics Performance Index of OPEC Countries with ENTROPY, CRITIC and LOPCOW-based EDAS Methods - Emre Kadir Özekenci (Journal of Transportation and Logistics)
The aim of this study is to examine the Logistics Performance Index (LPI) of the Organization of the Petroleum Exporting Countries(OPEC) using the ENTROPY, CRITIC, and LOPCOW-based EDAS method. Data were obtained from the "2018 report of LPI" issued by the World Bank (WB). To evaluate the logistics performance of the selected countries, six key dimensions—customs, infrastructure, international shipments, logistics quality and competence, tracking and tracing, and timeliness—were utilized. The weight of the criteria was calculated using three different weighting methods: ENTROPY, CRITIC, and LOPCOW. Subsequently, the countries were ranked using the EDAS method. The results from ENTROPY, CRITIC, and LOPCOW indicated that the most significant criteria were infrastructure, international shipments, and timeliness, respectively. The outcomes of the EDAS method revealed that the United Arab Emirates (UAE) and Angola exhibited the highest and lowest logistics performance, respectively. Additionally, the robustness and validity of the results were confirmed through comparative analysis.